Characteristics of high temperature C-CO2 gasification reactivity of Victorian brown coal char and its blends with high ash fusion temperature bituminous coal. (15th August 2017) - Dai, Baiqian; Hoadley, Andrew; Zhang, Lian
Graphical abstract: Highlights: Brown coal char has high reactivity due to porous structure. Catalytic effects from ash-forming elements insignificant 1100 °C onwards. Ash in the blends declines the reactivity by inhibiting gas diffusion. Synergism of coal/char blends is affected by bituminous coal. Abstract: This research paper explores the high temperature gasification reactivity of brown coal char and its potential for promoting the gasification of high-ash-fusion temperature bituminous coal under entrained-flow gasification conditions. Using thermogravimetric analysis (TGA), the C-CO2 gasification reactivity for a brown coal char and two bituminous coals with low/high ash contents and high ash fusion temperatures, as well as their blends were investigated over a temperature range of 900–1300 °C and atmospheric pressure. The n th order reaction rate equations were fitted based on a random pore model of the gasification reaction. The results show that the brown coal char has a high reactivity compared to the two bituminous coals, which mainly due to its more porous physical structure, whereas the catalytic effect of its ash-forming elements is insignificant above 1100 °C. The intrinsic activation energy was determined to be 154.5 kJ/mol for the brown coal char, which is lower than the higher activation energy of the two bituminous coals of 189.61 kJ/mol and 196.02 kJ/mol. Upon increasing the bituminous coal fraction, the activation energy increases stably due to the increased ash amount and increased molten ash that inhibit the gas diffusion. For the low-ash bituminous coal blended with 20–40% brown coal char, its C-CO2 reactivity is maximised at 1200 °C when the ash turns soft. Upon further increase of the temperature, its reactivity decreases due to the enhanced melting of the ash. Instead, for the high-ash bituminous coal, its addition of 20% to brown coal char is beneficial in decreasing the overall ash melting temperature. The C-CO2 gasification reactivity of 20% high-ash bituminous coal blended with brown coal char is maximised at 1100 °C when the ash turns soft and is minimised at 1200 °C when the ash is fully molten.